Choosing not to choose: when politicians choose to delegate powers - Voigt, Stefan; Salzberger, EliM. (2002)
Elected politicians often choose to delegate competence to various agencies rather than deciding themselves. The paper deals with the apparent paradox that competence is being transferred despite the fact that politicians are assumed to maximize individual utility. The constitutional structure, which is assumed to be exogenously given, serves as the independent variable in deriving hypotheses concerning delegation behavior as the dependent variable. Two categories of delegation can be distinguished: domestic delegation - to agencies within the legislators' jurisdiction - and international delegation - to supranational or international bodies. The choice of the body to which decision-making powers are transferred has rarely been analyzed within a unified framework. The paper deals with this issue. - Reproduced.
Keywords: Delegation of authority